Perfil dos pacientes com diagnóstico de câncer de mama atendidos num hospital em Aracaju, 2011 a 2015 - Barros, Pollyana de Souza (2017)
Breast cancer grows in Brazil with a high mortality rate associated with late diagnosis. To program prevention and early detection actions, it is necessary to know the profile of the patients affected. This study aimed to know the socio-demographic, clinical and histopathological profile of patients diagnosed with breast cancer, attended at a public hospital in Sergipe between 2011 and 2015. The medical records were reviewed and the diagnosis confirmed through the biopsy report. The participants had as main characteristics, aged between 46 and 55 years old, were from the home, residents of the state capital, presented menarche at age 12, had 1 to 2 children, were not smokers and had no history of neoplasia. They noticed alteration through self-examination of the breasts, with diagnosis of invasive ductal carcinoma, stage II, tumor size between 1 and 5 cm, mean time between suspicion and diagnosis 3 to 6 months.